Stability-Indicating RP-HPLC Method Development and Validation of Darunavir Using a Quality by Design (QbD) Approach, with Estimation in Prepared Solid Supersaturated Self-Emulsifying Drug Delivery Systems (SEDDS) - Sharannavar, Bhuvaneshwari; Deo, Apurva; Suryawanshi, Shailendra; Bhandurge, Parixit; Darbha, Nithyanand Sastry (International Journal of Pharmaceutical Investigation, 2026)
Background A new stability-indicating Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC) method was developed to quantify Darunavir (DRV), an HIV-1 protease inhibitor, despite its limited water solubility and susceptibility to light. Materials and Methods The method utilized the central composite design, aiming to minimize variations in regression coefficients. The primary objective of this study was to establish an RP-HPLC method that ensures accuracy, precision, and ease of automation. To date, there have been no recorded instances of utilizing methanol in RP-HPLC development. The focus was on demonstrating the cost-effectiveness of methanol in RP-HPLC method development, highlighting its economic advantages and good performance. The development and validation of HPLC methods are critical for various applications, including drug discovery, development, and manufacturing. DRV was analyzed at a wavelength of 267 nm utilizing a photodiode array detector, and separation of chromatographs was achieved using a Phenomenex Luna C-18 column. Results The mobile phase comprised methanol and HPLC-grade water (with 0.1% formic acid). The flow rate of the mobile phase was set at 1 mL/min, with an injection volume of 10 µL. The retention time for DRV was found to be 8.85 min. The force degradation data indicate decreases in basic, oxidation, and photolytic conditions; nevertheless, in thermal and acidic settings, a significant degree of stability was shown after 2 hr. Conclusion The study aimed to develop a simple, reliable reversed-phase HPLC method for quantifying DRV in pharmaceutical dosage forms and bulk drug samples.
Keywords: Darunavir; RP-HPLC; Central composite design; Analytical method validation